The Time of My Life: The Marketing Lessons From 'Dirty Dancing' - Omansky, Michael (Archives of Business Research, 2020)
“Dirty Dancing” was a movie with a major soundtrack. The soundtrack had a coordinated marketing effort, took on a life of its own but continued to succeed with guidance and control for over a decade. Its success contains many marketing lessons that can be applied to other projects.